Iracema na Transa Amazônica - Dias Filho, Cláudio Aurélio Leal (2013)
This study aims to analyze how the occupation of Brazilian Amazonia in the 70s was addressed in the film “Iracema Uma Transa Amazônica of Jorge Bodansky and Orlando Senna. The analysis is related to cultural theory and historical analyzes of the period of the military dictatorship. This bias allows a discussion of the representations of cultural identity and the conflicts that occurred within that process that marked the recent history of Brazil. The film is treated as a historical document, an element of production and reproduction of certain cultural and political values prevailing in society.